Janus Kinase Inhibitors in the Treatment of Crohn’s Disease and Ulcerative Colitis: A Review - Wiciun, Olympia; Skonieczna, Karolina; Ordon, Kacper; Badziąg, Magdalena; Szulc, Paulina; Kurczoba, Laura; Kłossowska, Martyna; Kądziołka, Olga (Quality in Sport, 2025)
Introduction and purpose: Insufficient efficacy and adverse effects of classical therapies for inflammatory bowel disease (IBD), such as ulcerative colitis and Crohn’s disease, have prompted the search for new, more targeted treatment methods. Janus kinase (JAK) inhibitors are a new group of oral drugs that modulate the proinflammatory cytokine signaling pathway. The aim of this review is to present the state of knowledge on the efficacy and safety of currently registered JAK inhibitors in the treatment of IBD. Review Methods: A systematic search of the PubMed database was conducted, focusing on publications from the last five years as well as selected key earlier studies. The search strategy included relevant keywords related to Janus kinase (JAK) inhibitors and inflammatory bowel disease (IBD). The most pertinent articles aligned with the study objective were reviewed and included. State of knowledge: JAK inhibitors, such as tofacitinib, upadacitinib, and filgotinib, have shown high efficacy in the treatment of moderate to severe UC and CD, especially in patients with insufficient biological therapy response. Clinical studies confirm their efficacy in inducing and maintaining remission and improving endoscopic findings. The most common adverse events are infections (including herpes zoster), and elevation of creatine kinase and lipids. The safety profile remains acceptable, although it requires monitoring, especially at higher doses, and further investigation. Summary: JAK inhibitors are an effective and promising therapeutic option for IBD, offering a rapid onset of action and good symptom control. Despite the favorable clinical effects, an individual approach to treatment and monitoring for adverse effects are necessary, especially with long-term use.